KOMUNIKASI STRATEGIS DALAM BISNIS SYARIAH UNTUK MENDUKUNG KETAHANAN PANGAN DAN ENERGI NASIONAL - Lidia Nuramalina; Faaris Luthfi Syhahiir (UIN Sunan Gunung Djati Bandung, 2025)
Food and energy security serve as vital foundations for the stability and independence of a nation. This article seeks to examine how strategic communication enhances the role of Sharia business in strengthening national food and energy resilience. Through a descriptive qualitative method that involves a literature review, the research investigates the incorporation of Islamic principles into business communication and the application of technology to boost the effectiveness of Sharia-oriented enterprises. The results indicate that Sharia business significantly contributes through agricultural finance, effective waqf management, and the promotion of renewable energy. Nonetheless, the complete realization of this potential is impeded by ineffective communication strategies and insufficient public knowledge regarding Islamic economics. Effectively planned strategic communication can influence public opinion, enhance collaboration among stakeholders, and increase the success of conveying Sharia-aligned values. Furthermore, collaboration among the government, financial organizations, businesses, and the community is vital for establishing a food and energy system that is inclusive, sustainable, and competitive. Consequently, reinforcing Islamic-based strategic communication and leveraging digital technology are crucial for amplifying the influence of Sharia economic development on national resilience.